SIFAT KIMIA DAN FISIK GULA CAIR DARI PATI UMBI GADUNG (Dioscorea hispida Dennts) [Chemical and Physical Properties of Liquid Sugar from Yam (Dioscorea hispida Dennts) Starch] - . Parwiyanti; Filli Pratama; Renti Arnita (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2011)
The objective of this research was to determine chemical and physical properties of liquid sugar made from yam starch (Dioscorea hispida Dennst) through enzymatic hydrolysis by using α-amylase. The experiment was designed as a Factorial Block Randomized Design with two factors and three replications. The first factor was concentrations of α-amylase (0.1, 0.3, and 0.5%), and the second was the time course of enzymatic hydrolysis (30, 60, 90, 120, and 150 min). The liquid sugar was analyzed in term of reducing sugar content, equivalent dextrose value, pH, and viscosity. The addition of different concentrations of α-amylase had significant effects (p >0.05) on reducing sugar contents and equivalent dextrose values. Enzymatic hydrolysis time course had significant effects (p >0.05) on reducing sugar content, equivalent dextrose values, pHs, and viscosity of the liquid sugar. The best liquid sugar was obtained by 0.5% α-amylase treatment for 60 min of hydrolysis. The liquid sugar had reducing sugar of 103.92 g/L, equivalent dextrose value of 34.64, pH of 5.36, and viscosity of 112.00 Poise.